Meio ambiente e com??rcio internacional: a OMC como vetor para os Objetivos de Desenvolvimento Sustent??vel (SDG) - Ferraz, Caroline Lima (2016)
Since the creation of international environmental law, the main discussion was the concept of economic development and environmental preservation. In developed countries, it began to emerge ecological movements that denounced the negative consequences of industrialization. In the other hand, in developing countries, governments were concerned that the imposition of rules to limit environmental degradation was a constraint to economic and social development. Consequently, it would not allow the reduction of poverty. In the WTO, the discussion between trade and environmental protection is to analyze the impact of environmental policies on trade and the effect of trade on the environment. Within this organization, much has been done for the sake of sustainable development. Although some panels have been opened based on the exceptions provided in Article XX, the creation of many non-tariff barriers can be a subterfuge to mask the free barriers trade. After more than 50 years of discussions, the only consensus on the preservation of the environment is that the Earth's temperature can not rise more than 2 ?? C in the coming years, as this would cause an environmental imbalance. For this, the United Nations launched the Sustainable Development Goals (SDGs), in order to promote clean economy and sustainable economic growth.